Pemanfaatan kulit sisa penyamakan untuk pakan ayam pedaging - Pencemaran, Kelompok Peneliti (Majalah Kulit, Karet, dan Plastik, 1984)
Research on utilization of tanneries leather waste product from fleshing for broiler fodder against production prestige is presented in this report. CRD system is applied this research using 150 chicken broiler, I day old. Mortality is not influenced by the experiment using fleshing waste product rich in proteineous substances